Reorienting the Quality Paradigm of Islamic Education in Modern Era: Challenges, Values, and Strategic Directions - Hilmi, Fahmi Firdaus; Ali, Moh. (LifeSciFi, 2026)
The quality of Islamic education in Indonesia faces significant challenges amid globalization, modernization, and rapid digital transformation. Current quality orientations emphasize technical-administrative standards and academic achievement, which do not fully reflect the core objectives of Islamic education. Therefore, a holistic, value-based reorientation of the quality paradigm grounded in Islamic principles is necessary. This study aims to identify the major challenges affecting the quality of Islamic education in the modern era, examine the urgency of a value-based paradigm reorientation, and formulate strategic directions for sustainable quality development along with their implications for educational policy and practice. This research employs a qualitative approach through a library research design, drawing on books, journal articles, and relevant academic literature. The collected data were analyzed using content analysis to synthesize key ideas and findings. The results reveal several major challenges, including curriculum dualism between religious and general sciences, limited innovation in learning practices, disparities in the quality of human resources, and weaknesses in institutional governance. The study concludes that reorienting the quality paradigm toward character formation, spiritual development, and the integration of Islamic values with science and technology is essential to strengthen the relevance and sustainability of Islamic education in contemporary society.